Childhood maltreatment and adult diseases in the general population: the mediating role of smoking and overweight in a time-sequence design - Klinger-König, Johanna; Streit, Fabian; Völker, Maja P.; Frank, Josef; Sekula, Peggy; Jaskulski, Stefanie; Leitzmann, Michael; Meinke-Franze, Claudia; Schmidt, Carsten O.; Keil, Thomas; Willich, Stefan N.; Pischon, Tobias; et al. (BMC public health, 2025)
Background Childhood maltreatment is associated with an unhealthier lifestyle in adulthood and an increased risk of mental and somatic health problems, although the underlying pathways remain unclear. This study examined whether smoking and overweight mediate the association between childhood abuse/neglect and frequent adult diseases, including cancer, myocardial infarction, stroke, type 2 diabetes, chronic obstructive pulmonary disease, depression, and anxiety. Methods Childhood maltreatment was assessed in 152,887 German National Cohort (NAKO) participants using the Childhood Trauma Screener. Information on smoking initiation age, weight history, and respective age at diagnosis was incorporated to ensure that smoking and overweight preceded the diagnosis. Mediation analyses were adjusted for age, sex, study center, and education. Results For childhood abuse, larger proportions of associations with adult somatic diseases were mediated through preexisting smoking and overweight compared to adult mental disorders. Smoking most strongly mediated myocardial infarction (36.88% [95% confidence interval (CI): 17.88%; 55.89%]), with more pronounced effects in men (48.62% [14.28%; 82.97%]) than in women (20.82% [2.75%; 38.89%]). For overweight, a substantial mediation was only found for type 2 diabetes (13.69% [9.85%; 17.52%]), with stronger effects in women (16.16% [8.92%; 23.39%]) compared to men (8.43% [4.52%; 12.35%]). Comparable results were found for childhood neglect. Conclusions To smoke or be overweight before the first diagnosis of myocardial infarction and type 2 diabetes mediated the association between childhood abuse/neglect and these somatic diseases. However, while the mediation through smoking and overweight contributed to the disease risk linked to childhood maltreatment, strong direct effects of childhood abuse/neglect persisted for both mental and somatic health problems. These findings underscore the need for further longitudinal studies to better understand the pathways.